MEASURES TO PROTECT THE ENVIRONMENT FROM THE HARMFUL EFFECTS OF MOTOR TRANSPORT (European Journal of Emerging Technology and Discoveries, 2024)
In this article, hybrid power devices, which are currently the most efficient in terms of economy and environmental parameters, are used: they work with an internal combustion engine on highways, and they work with an electric engine in urban areas, and a method of controlling the engine during idle running for cars in operation is developed using a software device implementation of cylinder deactivation according to a rational algorithm is shown.